Morphological studies of Different types of Hibiscus rosasinensis L. and Standradisation of Propagation Techniques - Verghese CA (Department of Pomology Floriculture and landscaping, College of Horticulture, 1987)
The investigation on collection, morphological description and standardization of propagation techniques of different types of hibiscus were carried out in the Department of Pomology and Floriculture, College of Horticulture, during the period 1979 to 1981. Thirty four types and fourteen varieties of Hibiscus rosasinensis, two types of H. schizopetalous and one type of H. mutabilis were collected from different zones of Kerala, Tamilnadu and Karnataka and were maintained in the College garden. Since the types collected had no specific varietal names, morphological descriptions of all the fifty one collections were made. Considerable variation both in vegetative and floral characters were exhibited by different types in the collection. A key was prepared based on important distinguishing characters for identification of different types of hibiscus, Acc.3, Acc.5, Acc.13, Acc.29, Acc.32, Acc.33, Acc.42 and Acc.52 were found to produce very attractive showy flowers of different shades of colours. Acc.43 and Acc.45 were bushy types. Pollen viability of ten types of hibiscus were studied. Considerable variation existed with regard to pollen viability among different types. Maximum pollen viability of 89.8 per cent was observed in Acc.22 and minimum of 4.7 per cent in Acc.7. Rooting of stem cuttings were assessed under two treatment conditions, with leaves and without leaves. Retention of leaves had significant influence over the treatment without leaves on rooting of cuttings. The response of growth regulators, IAA, IBA and NAA on rooting of ten hibiscus types were studied. It was revealed that in quick dip method best performance was recorded by NAA 3000 ppm followed by IBA 5000 ppm and IAA 10000 ppm for rooting percentage, number and length of roots. In prolonged dip method, higher rooting percentage, root number, root length and root weight was observed when cuttings were treated with NAA 50 ppm, IBA 75 ppm and IAA 100 ppm. Out of two methods of growth regulator application, quick dip method was significantly superior to prolonged dip method. The types responded differently to growth regulator treatment, Acc.19 responded best while least response was exhibited by Acc.7. From the studies on air layering, it was revealed that maximum rooting percentage of 89.3 was exhibited by Acc.38 and minimum percentage of success by Acc.7. Air layering recorded better rooting than cutting without growth regulator treatment. But, it showed lower rooting percentage when compared to growth regulator treated cuttings.